2019
DOI: 10.1002/adfm.201907063
|View full text |Cite
|
Sign up to set email alerts
|

Printed Conformable Liquid Metal e‐Skin‐Enabled Spatiotemporally Controlled Bioelectromagnetics for Wireless Multisite Tumor Therapy

Abstract: With inherent flexibility, high electroconductivity, excellent thermal conductivity, easy printability and biosafety, gallium-based functional liquid metals (LMs) have been increasingly evaluated for biomedical applications, especially as electronic skin (e-skin). Extending these versatile materials to more challenging applications is a worthwhile pursuit. To realize precise and spatiotemporal multisite tumor treatment under an alternating magnetic field (AMF), an oxidized GaIn (O-GaIn) mixture-based e-skin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 49 publications
0
131
0
Order By: Relevance
“…Rapid progress on the biomedical application of liquid metals (LM) has witnessed the tremendous research advance of these novel functional materials [ [1] , [2] , [3] , [4] , [5] ]. Simultaneously owning multi-properties such as high fluidity, excellent thermal and electrical conductivities, ideal biocompatibility, good radiopacity, controllable behaviors and conformability associated with reversible liquid-solid phase transition, facile manufacture and along with affordable cost, LM biomaterials have been widely applied in biological imaging [ 6 , 7 ], bone repair [ 8 ], drug delivery [ [9] , [10] , [11] ], magnetic hyperthermia [ 12 , 13 ], photothermal therapy [ [14] , [15] , [16] ], tumor embolotherapy [ 17 ], microwave dynamic therapy and microwave thermal therapy [ 18 ]. Such ‘One material, Multi-functionalities’ is rather unusual among many existing top materials and therefore it is noteworthy to recognize that a new direction of biomedical category: the LM biomaterials have formed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid progress on the biomedical application of liquid metals (LM) has witnessed the tremendous research advance of these novel functional materials [ [1] , [2] , [3] , [4] , [5] ]. Simultaneously owning multi-properties such as high fluidity, excellent thermal and electrical conductivities, ideal biocompatibility, good radiopacity, controllable behaviors and conformability associated with reversible liquid-solid phase transition, facile manufacture and along with affordable cost, LM biomaterials have been widely applied in biological imaging [ 6 , 7 ], bone repair [ 8 ], drug delivery [ [9] , [10] , [11] ], magnetic hyperthermia [ 12 , 13 ], photothermal therapy [ [14] , [15] , [16] ], tumor embolotherapy [ 17 ], microwave dynamic therapy and microwave thermal therapy [ 18 ]. Such ‘One material, Multi-functionalities’ is rather unusual among many existing top materials and therefore it is noteworthy to recognize that a new direction of biomedical category: the LM biomaterials have formed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Wang et al modified the adhesion properties of EGaIn by thorough oxidation. 91 After stirring in air, the adhesion between the LM and the skin increase drastically and the authors were able to write circuits directly on skin using a brush. They also demonstrated that these structures could be used for wireless thermotherapy by inducing a current with an alternated magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2A presented that the introduction of oxygen by agitation increases the content of gallium oxides and reduces the fluidity of gallium-based metals (Ga x In 1− x ). [1,49] The XPS images of eutectic GaInSn alloy (EGaInSn) revealed that the mixed oxides (Ga 2 O 3 ) were on the surface and elements In and Sn exhibited inner. [50] Since the natural environment contains enough oxygen, the mechanical strength of liquid metal droplets can be adjusted by controlling the degree of oxidation of the liquid metal.…”
Section: The Core-shell Structure Of Liquid Metalmentioning
confidence: 99%
“…Figure A presented that the introduction of oxygen by agitation increases the content of gallium oxides and reduces the fluidity of gallium‐based metals (Ga x In 1− x ). [ 1,49 ] The XPS images of eutectic GaInSn alloy (EGaInSn) revealed that the mixed oxides (Ga 2 O 3 ) were on the surface and elements In and Sn exhibited inner. [ 50 ]…”
Section: Interfacial Effects Of Liquid Metal In Gas Phasementioning
confidence: 99%